2006
DOI: 10.1111/j.1471-4159.2006.03734.x
|View full text |Cite
|
Sign up to set email alerts
|

Capacitative Ca2+ entry is involved in regulating soluble amyloid precursor protein (sAPPα) release mediated by muscarinic acetylcholine receptor activation in neuroblastoma SH‐SY5Y cells

Abstract: Previous studies have demonstrated that stimulation of phospholipase C-linked G-protein-coupled receptors, including muscarinic M 1 and M 3 receptors, increases the release of the soluble form of amyloid precursor protein (sAPPa) by a-secretase cleavage. In this study, we examined the involvement of capacitative Ca 2+ entry (CCE) in the regu- Slack et al. 1993Slack et al. , 1995Mills and Reiner 1999;Canet-Aviles et al. 2002). In addition, it has been suggested that other PKC-independent and Ca 2+ -dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Numerous studies have demonstrated that stimulation of phospholipase C-linked G-protein-coupled receptors, including muscarinic M1 and M3 receptors, increases the release of the sAPP␣ by ␣-secretase cleavage. The purpose of this research was to determine whether muscarinic receptor stimulation activates NF-B in neuroblastoma SH-SY5Y cells expressing abundant M3 muscarinic receptors and whether such muscarinic receptor-mediated NF-B activation is involved in sAPP␣ release and contributes to change the CCE, which our recent data (25) indicate plays an important role in the muscarinic receptor-mediated stimulation of sAPP␣ release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that stimulation of phospholipase C-linked G-protein-coupled receptors, including muscarinic M1 and M3 receptors, increases the release of the sAPP␣ by ␣-secretase cleavage. The purpose of this research was to determine whether muscarinic receptor stimulation activates NF-B in neuroblastoma SH-SY5Y cells expressing abundant M3 muscarinic receptors and whether such muscarinic receptor-mediated NF-B activation is involved in sAPP␣ release and contributes to change the CCE, which our recent data (25) indicate plays an important role in the muscarinic receptor-mediated stimulation of sAPP␣ release.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that various transcription factors are regulated by intracellular Ca 2ϩ movement (19,21,51). We observed that extracellular Ca 2ϩ influx (CCE) via SOC, which is functionally coupled with endoplasmic reticulum Ca 2ϩ depletion, plays a key role in muscarinic receptor-mediated sAPP␣ release (25). Thus, we attempted to characterize the nature of the Ca 2ϩ influx that participates in muscarinic receptor-mediated NF-B activation by administering Ca 2ϩ channel blockers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that the rTCTP-induced increase in [Ca 2+ ] i was due to a Ca 2+ influx from an extracellular source rather than via voltage-gated L-type Ca 2+ channels, and that rTCTP does not mobilize Ca 2+ from intracellular stores. Thapsigargin, an inhibitor of Ca 2+ -ATPase in the membranes of ER Ca 2+ stores, is generally used to inhibit refilling of Ca 2+ stores and subsequently depleting Ca 2+ from Ca 2+ stores in various cells [15,16], including PC12 cells. When PC12 cells were exposed to 1 µM thapsigargin in a Ca 2+ -containing buffer, it caused a sustained increase in [Ca 2+ ] i , confirming that intracellular Ca 2+ stores are releasable under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…They include the GABA B [27], group I metabotropic [42], chemoattractant [43], and muscarinic acetylcholine [44,45] receptors. However, the mechanism linking activated GPCRs to SOCs remains elusive.…”
Section: Discussionmentioning
confidence: 99%